Development and clinical application of phosphorus-containing drugs (2020)
Phosphorus-containing drugs belong to an important class of therapeutic agents and are widely applied in daily clinical practices. Structurally, the phosphorus-containing drugs can be classified into phosphotriesters, phosphonates, phosphinates, phosphine oxides, phosphoric amides, bisphosphonates, phosphoric anhydrides, and others; functionally, they are often designed as prodrugs with improved selectivity and bioavailability, reduced side effects and toxicity, or biomolecule analogues with endogenous materials and antagonistic endoenzyme supplements. This review summarized the phosphorus-containing drugs currently on the market as well as a few promising molecules at clinical studies, with particular emphasis on their structural features, biological mechanism, and indications.